2022
DOI: 10.3390/polym14132599
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Welan Gum on Montmorillonite and Its Influencing Factors

Abstract: Welan gum is one of the most promising polymers used in polymer flooding for enhancing oil recovery, due to its excellent temperature resistance and salt-tolerance performance. However, welan gum, as a polymer with higher molecular weight, can be adsorbed and detained in the pore throat of the reservoir, which is characterized by a smaller size. Montmorillonite, a kind of clay mineral with high content in reservoir rocks, has strong adsorption capacity. Therefore, the adsorption behavior of welan gum on montmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The study results indicated that the hydrogen bonding of ArG with clay is crucial in inhibiting clay swelling. The active constituents of ArG facilitate intercalating and adsorbing onto the clay surface via physicochemical interactions through hydrogen bonding [ 41 ]. Consequently, the protective layer of ArG makes the hydrophilic clay surface more water-resistant ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The study results indicated that the hydrogen bonding of ArG with clay is crucial in inhibiting clay swelling. The active constituents of ArG facilitate intercalating and adsorbing onto the clay surface via physicochemical interactions through hydrogen bonding [ 41 ]. Consequently, the protective layer of ArG makes the hydrophilic clay surface more water-resistant ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Montmorillonite (MMt) is a common inorganic phase in the synthesis of water-soluble polymer nanocomposites, and its nano-effects have received considerable research attention [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. MMt is a natural two-dimensional layered silicate material whose crystal structure is composed of two sheets of silicon–oxygen tetrahedra sandwiched between sheets of aluminum–oxygen octahedra [ 18 , 19 , 20 ]. The surface of a MMt layer has ample hydroxyl groups and negative charges, and abundant exchangeable ions exist between layers [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%